The Role of Probiotics in the Maintenance of Remission in Adult-Onset Crohn’s Disease: A Systematic Review - Maria Megapanou; Eleni Komninou; Evanthia Zampeli; Maria Gavriatopoulou; Theodora Psaltopoulou; Michael Liontos (Advanced Gut & Microbiome Research, 2025)
Conclusions: Although the role of probiotics in CD is doubted, this systematic review highlights the need for further research on the effect of probiotics on the microbiome profiles of IBD patients as well as large-scale, randomized controlled trials with standardized probiotic formulations, aiming at personalized probiotic therapies with valuable results in CD.